Kinetic-Spectrophotometric Determination of Trace Amounts of Va nadium(V) Based on its Catalytic Effect on the Reaction of o-Anisidine and Potassium Bromate - Andrews, B.S.A.; Sreenivas Rao, Battula; Shankar Dubey, Som; Malleswara Rao, D.; Venkat Kiran, B. (Asian Journal of Chemistry, 2011)
A simple and sensitive first order kinetic-spectrophotometric method is proposed for the determination of vanadium(V) in nanogram amounts. This method is based on the catalytic effect of vanadium(V) on the oxidation of o-anisidine by potassium bromate in acidic medium (HCl). The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of o-anisidine solution at 420 nm by fixed time method (20 min). The proposed method allows determination of vanadium in the range of 0.128-7.213 ng/mL with good precision and accuracy. The optimization of the operating conditions regarding concentrations of the reagents, temperature and interferences are also investigated. The reaction was found to be first order in o-anisidine, vanadium(V) and bromate. The rate of the reaction is found to have an inverse dependence on H+ concentration. The pseudo-first order rate constants are determined at different temperatures and thermodynamic parameters were evaluated. A possible mechanism has been proposed. The method was applied to the determination of vanadium(V) in meat sample, ground nut oil, seafood, black pepper and jack fruit. The results obtained were in excellent agreement with the standard methods such as atomic absorption spectrometry. The coefficient of variance and % error were in the range of 1.87- 3.26, 0.78-1.57 % respectively.